2012
DOI: 10.1017/s153759271200285x
|View full text |Cite
|
Sign up to set email alerts
|

Improbable but Potentially Pivotal Oppositions: Privatization, Capitalists, and Political Contestation in the Post-Soviet Autocracies

Abstract: Reflecting a chiefly economic approach to understanding political outcomes, a burgeoning literature on post-Soviet political economy finds a strong link between privatization and political pluralism in the region. To test whether the political promise of economic liberalization and the logic of modernization that underlies it hold true, I draw on existing and original data on privatization, pluralism, and opposition movements throughout the region from early independence to the present. The data reveal a funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 67 publications
0
8
0
4
Order By: Relevance
“…С. Радниц демонстрирует роль бизнес-элит в финансировании массовой мобилизации, приведшей к "цветным революциям" на постсоветском пространстве (Radnitz, 2010). Наличие у элит автономных ресурсов, полученных в результате приватизации, связывается с целым рядом политических исходов: коллапсом доминирующих партий (Greene, 2010), переходом представителей экономических элит в политическую оппозицию (Junisbai, 2012(Junisbai, , 2010, созданием оппозиционных межэтнических коалиций в африканских странах (Arriola, 2013).…”
Section: исследования политики и бизнеса: международная повесткаunclassified
See 1 more Smart Citation
“…С. Радниц демонстрирует роль бизнес-элит в финансировании массовой мобилизации, приведшей к "цветным революциям" на постсоветском пространстве (Radnitz, 2010). Наличие у элит автономных ресурсов, полученных в результате приватизации, связывается с целым рядом политических исходов: коллапсом доминирующих партий (Greene, 2010), переходом представителей экономических элит в политическую оппозицию (Junisbai, 2012(Junisbai, , 2010, созданием оппозиционных межэтнических коалиций в африканских странах (Arriola, 2013).…”
Section: исследования политики и бизнеса: международная повесткаunclassified
“…Роль бизнес-акторов в политике и взаимоотношения власти и бизнеса -не новые сюжеты в политической науке. Бизнес играет значительную роль в поддержании и подрыве стабильности авторитарных режимов (Arriola, 2013;Junisbai, 2012;Radnitz, 2010), экономическая автономия связывается с переходом к демократии и её эффективным функционированием (Dahl, 1971;Moore, 1966), a многочисленные стратегии лоббирования и влияния на политику представляют собой отдельное поле исследований на стыке политологии и менеджмента (Hansen & Mitchell, 2000;Lux et al, 2011). Этот интерес неудивителен, если принять во внимание наличие у бизнеса ресурсов, независимых от государства, и интересов, зачастую расходящихся с целями государственного регулирования и действиями авторитарных правителей.…”
unclassified
“…Cross-national quantitative studies have argued that defections are caused by economic crisis (Haggard and Kaufman 1995;Reuter and Gandhi 2011). Qualitative case studies, meanwhile, have focused either on the role of electoral competition (Langston 2006), economic liberalization (Balmaceda 2013;Junisbai 2012;Radnitz 2010), or the contextual strategies used by autocrats (Khisa 2016;Schedler and Hoffmann 2016).…”
Section: Authoritarian Stability and Elite Cohesionmentioning
confidence: 99%
“…Studies on post-Soviet economies showed that state insiders, as managers of economic units and civil servants, diffused into the ownership structures of key industries through de-regulation and privatisation. While inter-elite conflicts have led to opaque allocation mechanisms, authoritarian political regimes are progressively entrenched whereby ruling elites increased their ownership and/or political control of the key industrial assets (Junisbai, 2012;Özcan, 2010). In a study of Russia's largest oligarchs, Guriev and Rachinsky (2005) illustrate how the concentration of ownership of large industrial establishments served the highly corrupt political regime in which neither oligarchs nor the bureaucracy are interested in implementing policies that will open the economy to broader participation, fair allocation and competition.…”
Section: Analytical Frameworkmentioning
confidence: 99%